Representasi Penyimpangan Agama dalam Web Series Bidaah - Irfan, M.; Azizah, Nurul (Program Studi Komunikasi dan Penyiaran Islam (KPI) Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH), 2025)
Web series, also known as web series, are a rapidly growing form of digital media. One phenomenal web series that has captured public attention is the Malaysian web series